Evaluasi Rating dan Online Customer Review terhadap Keputusan Pembelian Pengguna Shopee - Mochamad Husein Isnaeini; Hani Hasanah; Verawati Fajrin (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to evaluate ratings and online customer reviews on shopee users' purchasing decisions. The population used in this study were all users of the Indonesian shopee marketplace using a sample of 120 shopee users. The respondent selection technique in this study used a non-probability sampling technique with an incidental sampling type. Data collection in this study used a digital questionnaire (google form). This study used a quantitative method with data analysis techniques for convergent validity tests, reliability tests, discriminant validity tests, multicollinearity tests, r-square tests, and hypothesis tests. The results of this study indicate that ratings have a significant effect on purchasing decisions of 6.508> Zscore 1.96 and online customer reviews have a significant effect on purchasing decisions of 16.615> Zscore 1.96. The r-square test shows that ratings and online customer reviews simultaneously influence purchasing decisions by 88.1%.